Ecology of endolithic lichens colonizing granite in continental Antarctica - Ríos, Asunción de los; Wierzchos, Jacek; Sancho, Leopoldo G.; Green, Allan; Ascaso, Carmen (The Lichenologist, 2005)
13 pages,tables statistics, figures and photos In this study, the symbiont cells of several endolithic lichens colonizing granite in continental Antarctica and the relationships they have with the abiotic environment were analyzed in situ, in order to characterize the microecosystems integrating these lichens, from a microecological perspective. Mycobiont and photobiont cells, the majority classified as living by fluoresecent vitality testing, were observed distributed through the fissures of the granite. The fact that extracellular polymeric substances were commonly observed close to these cells and the features of these compounds, suggest a certain protective role for these substances against the harsh conditions of the environment. Different chemical, physical and biological relationships take place within the endolithic biofilms where the lichens are found, possibly affecting also the survival and distribution of these organisms. The alteration of bedrock minerals and synthesis of biominerals in the proximity of these lichens gives rise to different chemical microenvironments and suggests their participation in mineral nutrient cycling. Peer reviewed